2011
DOI: 10.1080/10286020.2011.619183
|View full text |Cite
|
Sign up to set email alerts
|

Alliumonoate: a new cyclopentane derivative fromAllium victorialis

Abstract: Alliumonoate, a new cyclopentane derivative, has been isolated from the chloroform-soluble fraction of the ethanolic extract of Allium victorialis, along with β-amyrin acetate, β-sitosterol acetate, 22-cyclohexyl-1-docosanol, β-amyrin, β-sitosterol, and β-sitosterol 3-O-β-D-glucopyranoside, reported for the first time from this species. Their structures were elucidated on the basis of spectral data including mass spectra and 2D NMR experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Allivictoside A-H 51 Allumine A and B, Cyclopent-1-enecarboxylate, 52 22-Cyclohexyl-1-docosanol, Alliumonoate, β-Sitosterol acetate, β-Amyrin, β-Amyrin acetate, β-Sitosterol, β-Sitosterol 3-O-b-Dglucopyranoside 53 Anti-neuroinflammatory effects 51 Chemopreventive and anticancer activities 54 Anti-diabetic activity 55 Allium vineale Deltonin, Ophiopogonin C and 7 other saponins 56 Allyl methyl disulfide, 1-Propenyl propyl disulfide, Dimethyl trisulfide, 2-Furaldehyde, 2,4-Dimethylthiophene, Benzaldehyde, (2E)-Hexenal, (3Z)-Hexenol, Methyl (Z)-1propenyl disulfide, Methyl (E)-1-propenyl disulfide, Diallyl disulfide, Allyl (Z)-1-propenyl disulfide, Allyl (E)-1-propenyl disulfide, Methyl (methylthio)methyl disulfide, Allyl methyl trisulfide, 4-Methyl-1,2,3-trithiolane, Methyl propyl trisulfide, Methyl (Z)-1-propenyl trisulfide, Methyl (E)-1-propenyl trisulfide, Dimethyl tetrasulfide, Allyl (methylthio)methyl disulfide, Diallyl trisulfide, Allyl (Z)-1-propenyl trisulfide, p-Vinylguaiacol, Allyl propyl trisulfide, 5-Methyl-1,2,3,4tetrathiane, Methyl (methylthio)methyl trisulfide, 4-Methyl-1,2,3,5,6-pentathiepane, Allyl methyl tetrasulfide 57 Diosgenin, Nuatigenin and Isonuatigenin 56 Antioxidant activity 57 Biological activity Numerous pharmacological studies have revealed that Allium species exhibit a variety of exciting activities, including cytotoxic, antioxidant, thrombolytic, antibacterial, and other beneficial effects.…”
Section: Allium Victorialismentioning
confidence: 99%
“…Allivictoside A-H 51 Allumine A and B, Cyclopent-1-enecarboxylate, 52 22-Cyclohexyl-1-docosanol, Alliumonoate, β-Sitosterol acetate, β-Amyrin, β-Amyrin acetate, β-Sitosterol, β-Sitosterol 3-O-b-Dglucopyranoside 53 Anti-neuroinflammatory effects 51 Chemopreventive and anticancer activities 54 Anti-diabetic activity 55 Allium vineale Deltonin, Ophiopogonin C and 7 other saponins 56 Allyl methyl disulfide, 1-Propenyl propyl disulfide, Dimethyl trisulfide, 2-Furaldehyde, 2,4-Dimethylthiophene, Benzaldehyde, (2E)-Hexenal, (3Z)-Hexenol, Methyl (Z)-1propenyl disulfide, Methyl (E)-1-propenyl disulfide, Diallyl disulfide, Allyl (Z)-1-propenyl disulfide, Allyl (E)-1-propenyl disulfide, Methyl (methylthio)methyl disulfide, Allyl methyl trisulfide, 4-Methyl-1,2,3-trithiolane, Methyl propyl trisulfide, Methyl (Z)-1-propenyl trisulfide, Methyl (E)-1-propenyl trisulfide, Dimethyl tetrasulfide, Allyl (methylthio)methyl disulfide, Diallyl trisulfide, Allyl (Z)-1-propenyl trisulfide, p-Vinylguaiacol, Allyl propyl trisulfide, 5-Methyl-1,2,3,4tetrathiane, Methyl (methylthio)methyl trisulfide, 4-Methyl-1,2,3,5,6-pentathiepane, Allyl methyl tetrasulfide 57 Diosgenin, Nuatigenin and Isonuatigenin 56 Antioxidant activity 57 Biological activity Numerous pharmacological studies have revealed that Allium species exhibit a variety of exciting activities, including cytotoxic, antioxidant, thrombolytic, antibacterial, and other beneficial effects.…”
Section: Allium Victorialismentioning
confidence: 99%